The Effect of ChatGPT Use on Optimizing the Scientific Writing Process for Javanese Language and Literature Students at Unnes - Amirul Nuswantara Adli; Nur Hanifah Insani; Eka Yuli Astuti (Journal of Education Reseach and Evaluation, 2026)
The use of artificial intelligence technology, particularly ChatGPT, has become increasingly widespread in academic activities and has influenced the way students compose scientific papers. However, research on the use of ChatGPT in the context of academic writing among students of Javanese Language and Literature remains very limited. This study aims to analyze the effect of ChatGPT usage on optimizing the scientific writing process of Javanese Language and Literature students. This research employed a quantitative approach with a correlational research design. The subjects consisted of 100 Javanese Language and Literature students selected randomly from a population of 366 students. Data were collected using a Likert-scale questionnaire comprising 25 items. The results of the analysis indicated that the data were normally distributed, the relationship between variables was linear, and there was a strong positive correlation between the use of ChatGPT and the optimization of scientific writing. The partial t-test showed that ChatGPT helped improve the clarity of arguments, the structure of writing, and grammatical accuracy. The findings also revealed that students utilized ChatGPT to support idea development and enhance writing efficiency. In conclusion, the use of ChatGPT significantly contributes to optimizing the scientific writing process of students, particularly in terms of idea organization, language accuracy, and time efficiency. The implications suggest the need to integrate ChatGPT as a guided and ethical learning tool in academic writing curricula to improve students’ academic literacy without compromising the originality of their work.